Comparison of the Molecular Tests - Single PCR, Nested PCR and Quantitative PCR (SYBR Green and TaqMan) - For Detection of Phaemoniella Chlamidospora During Grapevine Nursery Propagation - Edwards, J.; Constable, F.; Wiechel, T.; Salib, S. (Phytopathologia Mediterranea, 2007)
Water, callus media and plant material were sampled from commercial nurseries during two propagating seasons: 2003 and 2005. Various methods were tested for their ability to detect Phaeomoniella chlamydospora in the samples. Nested PCR and quantitative PCR were the most sensitive, although further research is required to optimise their use. When molecular techniques were used, all water samples tested positive for P. chlamydospora, indicating that the grapevine propagation process is a potential source of infection.